2019
DOI: 10.1161/circulationaha.118.038179
|View full text |Cite
|
Sign up to set email alerts
|

Survival in Out-of-Hospital Cardiac Arrest After Standard Cardiopulmonary Resuscitation or Chest Compressions Only Before Arrival of Emergency Medical Services

Abstract: Survival after different forms of bystander cardiopulmonary resuscitation in out-of-hospital cardiac arrest THESIS FOR DOCTORAL DEGREE (Ph.D.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
1
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(89 citation statements)
references
References 162 publications
(233 reference statements)
4
77
1
7
Order By: Relevance
“…These may include: poverty, poor diet (potentially leading to obesity and diabetes), higher incidence of smoking and higher rates of mental illness. [4][5][6][7] Bystander Cardiopulmonary Resuscitation (BCPR) can double the chance of survival from OHCA [8], yet it is performed less often in deprived communities. Findings from Scotland indicate that people living in deprived areas are both more likely to have a cardiac arrest and more likely to have a cardiac arrest earlier in comparison to individuals living in less deprived areas.…”
Section: Introductionmentioning
confidence: 99%
“…These may include: poverty, poor diet (potentially leading to obesity and diabetes), higher incidence of smoking and higher rates of mental illness. [4][5][6][7] Bystander Cardiopulmonary Resuscitation (BCPR) can double the chance of survival from OHCA [8], yet it is performed less often in deprived communities. Findings from Scotland indicate that people living in deprived areas are both more likely to have a cardiac arrest and more likely to have a cardiac arrest earlier in comparison to individuals living in less deprived areas.…”
Section: Introductionmentioning
confidence: 99%
“…Recently Riva et al found there was an almost a 2-fold higher rate of CPR before EMS arrival and a concomitant 6-fold higher rate of CO-CPR over time but did not collect neurological outcome at day 30. 25 Lay bystanders are more and more often performing CO-CPR From 2013 to 2017, we observed a clear decrease in S-CPR by lay bystanders to the bene t of CO-CPR (reduction of 50%). The same trends were observed in Sweden during the same period, 25 and it has also been observed in other countries.…”
Section: Discussionmentioning
confidence: 72%
“…25 Lay bystanders are more and more often performing CO-CPR From 2013 to 2017, we observed a clear decrease in S-CPR by lay bystanders to the bene t of CO-CPR (reduction of 50%). The same trends were observed in Sweden during the same period, 25 and it has also been observed in other countries. 11,15,16 Indeed, since 2010, the International Consensus on Cardiopulmonary Resuscitation has been encouraging untrained people to carry out CO-CPR, and EMS dispatchers must provide CO-CPR instructions by telephone.…”
Section: Discussionmentioning
confidence: 72%
“…Fatalerweise haben viele Ersthelfer dann nicht nur auf die Beatmung, sondern konsekutiv auch auf die Herzdruckmassage verzichtet. Die Reduktion auf die Herzdruckmassage und damit auf die 3 Schritte Prüfen.Rufen.Drücken kann diesem entgegenwirken und die Rate an Laienreanimationen signifikant steigern [32,33].…”
Section: Materials Und Methodenunclassified